Caregivers' perceptions of the relationship among weight, health status, and asthma in their children. (December 2021) - Bianchi-Hayes, Josette M; Cataldo, Rosa; Schoenfeld, Elinor R; Hou, Wei; Pati, Susmita
Asthma and obesity are the two most common childhood illnesses and are physiologically interrelated. Few studies have assessed parental perceptions and beliefs about this relationship to better target education and therapy. This study aimed to determine caregiver beliefs and perceptions regarding weight, health status, and asthma diagnoses. Data from a survey of caregivers to children aged 4–11 years are merged with corresponding anthropometric and medical data from the electronic medical record. Caregivers of children with asthma completed a supplemental questionnaire. Univariable and multivariable logistic regressions were used to evaluate associations between perception of health problem, asthma, and weight status. Increased weight status was ≥ 85th body mass index percentile per Centers for Disease Control classifications. Compared to caregivers of healthy children and those of children with healthy weight and asthma, caregivers of dual diagnosis children were more likely to identify weight as a health problem (OR = 3.89, 95% confidence interval [1.48, 10.21]). Nevertheless, only 31% of caregivers of children with dual diagnosis believed weight contributed to the severity of their child's asthma. Less than one third of caregivers of dual diagnosis children believed that these diagnoses are interrelated. Addressing this gap in understanding is a critical next step to developing family-centered interventions.